Pengaruh Green Marketing dan Inovasi Produk Terhadap Keputusan Pembelian di Dusun Bambu Bandung - Baroka Herlambang; Indah Nur Agustiani; Khoirul Fajri (Manajemen dan Pariwisata, 2023)
This research was conducted at the Dusun Bambu Bandung tourist spot, the aim was to examine the effect of green marketing and product innovation on purchasing decisions. This study uses validity, reliability and normality test instruments with descriptive and verification analysis to prove the hypotheses that have been made.The results of this study indicate that there is a relationship between green marketing on purchasing decisions with an effect of 59.1%, there is a relationship between product innovation on purchasing decisions with an influence of 48.4% and finally there is an influence between green marketing and product innovation simultaneously on decisions purchase by 40%. This proves that green marketing factors and product innovation are factors that influence purchasing decisions.